Differences and Similarities of Central Asian, African, and Arctic Dust Composition from a Single Particle Perspective - Konrad Kandler; Kilian Schneiders; Johannes Heuser; Andebo Waza; Sudharaj Aryasree; Dietrich Althausen; Julian Hofer; Sabur F. Abdullaev; Abduvosit N. Makhmudov (Atmosphere, 2020)
Mineral dust composition affects a multitude of processes in the atmosphere and adjacent compartments. Dust dry deposition was collected near source in northwest Africa, in Central Asia, and on Svalbard and at three locations of the African outflow regime. Samples were subjected to automated scanning electron microscopy with energy-dispersive X-ray analysis to obtain size and composition of 216,000 individual particles. Results show low temporal variation in estimated optical properties for each location, but considerable differences between the African, Central Asian, and Arctic regimes. No significant difference was found between the K-feldspar relative abundances, indicating comparable related ice-nucleation abilities. The mixing state between calcium and iron compounds was different for near source and transport regimes, potentially in part due to size sorting effects. As a result, in certain situations (high acid availability, limited time) atmospheric processing of the dust is expected to lead to less increased iron solubility for near-source dusts (in particular for Central Asian ones) than for transported ones (in particular of Sahelian origin).